Traffic light control for multi-junctions - Chan, Rebecca (2014)
This project mainly focuses on the collection of data for traffic light controls in multi-junction area. As the population grows tremendously in Singapore, it has become increasingly important to do data collection and improve road conditions to provide a better road journey. The Clementi area, along the Commonwealth Avenue, was being evaluated for six continuous junctions during the peak hour of 8am to 9am as this part of the road is heavily used and usually congested at this hour.